1
$\begingroup$

If we take a Hamiltonian density to be as following

$$ \mathscr{H}=\frac{1}{2}\Pi^2+\frac{1}{2}\partial_i\varphi\partial_i\varphi+\frac{1}{2}m^2\varphi^2+\frac{1}{4}\lambda\varphi^4, $$

and we have the following action

$$ \mathcal{S}=\int \mathrm{d}^{d+1}x(\Pi\dot\varphi-\mathscr{H}). $$

How am I suppose to calculate

$$ \delta\mathcal{S}=\int\mathrm{d}^{d+1}x\frac{\delta\mathcal{S}[\varphi]}{\delta\varphi(x)}\delta\varphi(x)+\dots $$

and

$$ \delta\mathcal{S}=\int\mathrm{d}^{d+1}x\frac{\delta\mathcal{S}[\Pi]}{\delta\Pi(x)}\delta\Pi(x)+\dots $$

For example with $\varphi$:

$$ \frac{\delta\mathcal{S}[\varphi(x)]}{\delta\varphi(x)}=\int\mathrm{d}^{d+1}y\frac{\delta}{\delta\varphi(x)}(\Pi\dot\varphi+\mathscr{H}), $$

which gives me

$$ \frac{\delta\mathcal{S}[\varphi(x)]}{\delta\varphi(x)}=\int\mathrm{d}^{d+1}y\left(\partial_0(\Pi\delta^{d+1}(x-y))-\dot\Pi\delta^{d+1}(x-y)-\frac{\delta\mathscr{H}}{\delta\varphi(x)}\right). $$

I know I am supposed to get to the Hamilton's equations

$$\dot\Pi=-\frac{\delta\mathcal{H}}{\delta\varphi}$$

where $$\mathcal{H}=\int\mathrm{d}^{d}x\mathscr{H},$$ but it seems like it won't work.

$\endgroup$
0
$\begingroup$

I think I came up with a solution: $$ \frac{\delta\mathcal{S}[\varphi]}{\delta\varphi(x)}={\frac{\delta}{\delta\varphi(x)}\int\mathrm{d}^{d+1}y\left(\Pi\dot\varphi-\mathscr{H}\right)\nonumber\\ =\frac{\delta}{\delta\varphi(x)}\int\mathrm{d}^{d+1}y\left(\Pi\dot\varphi\right)-\frac{\delta}{\delta\varphi(x)}\int\mathrm{d}^{d+1}y\mathscr{H}\nonumber\\ =-\frac{\delta}{\delta\varphi(x)}\int\mathrm{d}^{d+1}y\left(\Pi\dot\varphi\right)-\frac{\delta}{\delta\varphi(x)}\int\mathcal{H}\mathrm{d} t+\underbrace{\text{boundary terms}}_\textrm{=0}\nonumber\\ =-\int\mathrm{d}^{d+1}y\left(\dot\Pi\frac{\delta\varphi}{\delta\varphi(x)}\right)-\int\frac{\delta\mathcal{H}}{\delta\varphi(x)}\mathrm{d} t\nonumber\\ =-\int\mathrm{d}^{d+1}y\left(\dot\Pi\delta^{d}(x-y)\right)-\int\frac{\delta\mathcal{H}}{\delta\varphi(x)}\mathrm{d} t\nonumber\\ =\int\left(-\dot\Pi-\frac{\delta\mathcal{H}}{\delta\varphi(x)}\right)\mathrm{d} t\nonumber.} $$ Since the variation of the action must vanish, it implies that $$ -\dot\Pi-\frac{\delta\mathcal{H}}{\delta\varphi}=0 \implies \dot\Pi=-\frac{\delta\mathcal{H}}{\delta\varphi}, $$ as desired. We can do exactly the same for the $\Pi$ equation.

| cite | improve this answer | |
$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.